The Baeyer–Villiger rearrangement with metal triflates: new developments toward mechanism. Issue 36 (4th June 2020) - Latos, Piotr; Siewniak, Agnieszka; Sitko, Magdalena; Chrobok, Anna
Abstract : New insight into the mechanism of Baeyer–Villiger oxidation with H2 O2 and metal triflates was presented. Abstract : Based on MS analysis, the mechanism of the Baeyer–Villiger oxidation of cyclic ketones with hydrogen peroxide using metal triflates (Ga(OTf)3 and Er(OTf)3 ) as catalysts was proposed. In the case of cyclohexanone as a substrate, dimeric, trimeric and tetrameric peroxide structures were detected.